POLITISASI HAK PENGELOLAAN (HPL) DALAM SISTEM HUKUM PERTANAHAN NASIONAL - Bambang Sadono (Faculty of Law, Universitas Diponegoro, 2010)
To facilitate the economic development, the government of the New Order era (1966-1998) practised the Agrarian Law politicization. Politicization of the policy include In setting the Management Authority (Hak Pengelolaan-HPL). HPL has no legal basis in accordance with the hierarchy of procedural legislation, and in substance are also contrary to the fundamental purpose of basic regulation. As a result, causes a lot of controversy and problems in practice. Many cases due to HPL, happens every where. The presence of HPL should be straightened out, especially in term of legal system, given the correct legal basis, or eliminated altogether